Regulated Secretion in Endothelial Cells: Biology and Clinical Implications - Datta, Yvonne H.; Ewenstein, Bruce M. (Thrombosis and Haemostasis, 2001)
Regulated secretion provides a means by which endothelial cells (EC) can rapidly and selectively alter the microenvironment of individual vascular beds, and modulate the interrelated processes of coagulation, fibrinolysis, and inflammation. The rapid release of high molecular weight multimers of von Willebrand factor (VWF) and surface expression of P-selectin in response to a wide variety of stimuli have been well documented, and are the result of exocytosis of Weibel-Palade bodies (WPB). The regulated release of other EC secretory proteins, including tissue plasminogen activator (tPA), interleukin-8, endothelin-1, and multimerin, has also been described. New light is being shed on how secretory proteins are selectively targeted to storage granules in EC, and on the molecular and cellular events that comprise regulated secretion. Knowledge of the mechanisms of sorting and secretion from EC storage granules may provide basis for new strategies for treating inflammatory and coagulation disorders.
Keywords: Endothelial cells; secretion; Weibel-Palade bodies; coagulation; inflammation